PENGARUH KOMPENSASI FINANSIAL DAN NON FINANSIAL TERHADAP KINERJA KARYAWAN CV FENARU JAYA - Resti Riandi; Irsyadi Zain (Ensiklopedia Social Review, 2021)
The purpose of this study was to determine the effect of financial compensation and non-financial compensation variables on employee performance and the effect of job satisfaction on employee performance at CV Fenaru Jaya. . The method used is descriptive and multiple linear regression path analysis. From the results of the study, it is known that financial and non-financial compensation have a positive and significant effect on employee performance.